Interleukin‐33 is a Novel Immunosuppressor that Protects Cancer Cells from TIL Killing by a Macrophage‐Mediated Shedding Mechanism. Issue 21 (5th September 2021) - Wu, Jing; Chen, Ziqing; Wickström, Stina L.; Gao, Juan; He, Xingkang; Jing, Xu; Wu, Jieyu; Du, Qiqiao; Yang, Muyi; Chen, Yi; Zhang, Dingding; Yin, Xin; et al.
Abstract: Recognition of specific antigens expressed in cancer cells is the initial process of cytolytic T cell‐mediated cancer killing. However, this process can be affected by other non‐cancerous cellular components in the tumor microenvironment. Here, it is shown that interleukin‐33 (IL‐33)‐activated macrophages protect melanoma cells from tumor‐infiltrating lymphocyte‐mediated killing. Mechanistically, IL‐33 markedly upregulates metalloprotease 9 (MMP‐9) expression in macrophages, which acts as a sheddase to trim NKG2D, an activating receptor expressed on the surface of natural killer (NK) cells, CD8+ T cells, subsets of CD4+ T cells, iNKT cells, and γδ T cells. Further, MMP‐9 also cleaves the MHC class I molecule, cell surface antigen‐presenting complex molecules, expressed in melanoma cells. Consequently, IL‐33‐induced macrophage MMP‐9 robustly mitigates the tumor killing‐effect by T cells. Genetic and pharmacological loss‐of‐function of MMP‐9 sheddase restore T cell‐mediated cancer killing. Together, these data provide compelling in vitro and in vivo evidence showing novel mechanisms underlying the IL‐33‐macrophage‐MMP‐9 axis‐mediated immune tolerance against cancer cells. Targeting each of these signaling components, including IL‐33 and MMP‐9 provides a new therapeutic paradigm for improving anticancer efficacy by immune therapy. Abstract : T cells execute specific killing effects on cancer cells through recognition of cell surface molecules expressed in both cells. This article shows that interleukin‐33‐stimulated macrophages produce MMP‐9 that eliminates cell surface molecules in immune cells and cancer cells. Through this mechanism, MMP‐9 debilitates the T cell‐medicated anticancer effects.